2018
DOI: 10.1002/prep.201800235
|View full text |Cite
|
Sign up to set email alerts
|

Emission Spectroscopy of the Combustion Flame of Aluminium/Copper Oxide Thermite

Abstract: The combustion process of stoichiometric aluminium/copper(II)oxide thermite was experimentally investigated in an optical bomb under inert atmosphere (N2) and ambient pressure. The reaction zone was monitored with UV/VIS emission spectroscopy and a colour high‐speed camera. The emission spectra were analysed by modelling of the background radiation and the characteristic emission of all molecular emitters in the reaction of Al/CuO. Based on this, the particles′ surface and gas phase temperature, the emissivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Furthermore, some authors reported FeO emission in meteoric ablation measurements and a terrestrial night airglow spectrum [8,9] as well as in experiments with induced emission on steel surfaces [10]. On the other hand, other authors reported spectral features at 605 nm and 615 nm as copper oxide (CuO) [11,12], and recently, Knapp et al [13] proposed a model of this diatomic molecule. We were unable to find reports related with Fe 3 O 4 spectral emissions in the VIS-NIR spectral regions for combustion processes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some authors reported FeO emission in meteoric ablation measurements and a terrestrial night airglow spectrum [8,9] as well as in experiments with induced emission on steel surfaces [10]. On the other hand, other authors reported spectral features at 605 nm and 615 nm as copper oxide (CuO) [11,12], and recently, Knapp et al [13] proposed a model of this diatomic molecule. We were unable to find reports related with Fe 3 O 4 spectral emissions in the VIS-NIR spectral regions for combustion processes.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, that the orange color of the incandescent spark could partly be caused by emission of copper oxide in the orange/red region, which is hardly distinguishable from orange/red black body emission by eye. The color of hot burning Al/CuO thermite mixtures based on the emission of CuO and Cu 2 in the gas phase has been investigated in detail in literature . The identification of surface combustion according to Glassman's criterion is not straightforward in the case of Cu sparks, as CuO decomposes and the boiling point is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The color of hot burning Al/CuO thermite mixtures based on the emission of CuO and Cu 2 in the gas phase has been investigated in detail in literature. [34] The identification of surface combustion according to Glassman's criterion is not straightforward in the case of Cu sparks, as CuO decomposes and the boiling point is unknown. But the boiling point of Cu is strongly above Gordon's limit for class A and its oxidation is only slightly exothermic, consequently surface combustion can be expected and is confirmed by the structure of the thin spark.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, multivariate techniques were implemented to detect weak spectral emission profiles. The application of PCA and the analysis of loadings of the combustion spectra of chalcopyrite, allowed us to find peaks at 606 and 616 nm, which are associated with copper oxides [19,20]. These peaks were observed slightly from the loading of the PC3 of the CpyD sample, being more visible in the CpyF sample (Figure 4d-f).…”
Section: Spectral Measurement From Chalcopyritementioning
confidence: 98%
“…The study presented by Gole in the early 1990s was the first to report the emission profile of copper oxide, with spectral bands located in the range of 580 to 720 nm [19]. For their part, Knapp et al proposed a spectral profile of copper oxide and aluminum oxide in their study of the emission spectroscopy of the termite combustion flame [20]. In this study, they presented four peaks located at 606, 616, 629 and 640 nm, which represent CuO x emissions.…”
Section: Spectral Emission Of Cuo Xmentioning
confidence: 99%